Pendampingan Wirausaha di Kawasan Kuliner Kelurahan Ledok, Kecamatan Argomulyo Kota Salatiga - Henry Yuliamir; Enik Rahayu; Alleta Dewi Maria (Universitas 45 Surabaya, 2023)
The project involves a series of training and consultations facilitated by a team of experts experienced in business management, marketing and entrepreneurship. During the mentoring period, culinary entrepreneurs receive the knowledge and practical skills necessary to increase their operational efficiency, improve product quality and expand market reach. In addition, they are also involved in collaborative sessions that encourage the exchange of ideas and experiences between entrepreneurs in the region. The results of this assistance include improving menu quality, improvements in financial and inventory management, as well as improvements in marketing and branding of culinary businesses. Participants also reported an increase in their income and increased competitiveness in the local culinary market. Apart from the positive economic impact, this assistance also provides social benefits by strengthening the local culinary entrepreneurial community and encouraging collaboration between them. These steps aim to maintain sustainable positive development in the Ledok Village culinary area and provide inspiration for the development of micro and small businesses in the surrounding area. Thus, the